RISK FACTORS OF EARLY CARDIOVASCULAR PATHOLOGY OF CHILDREN SUFFERING FROM JUVENILE RHEUMATIC ARTHRITIS - E.Yu. Gudkova; E.I. Alexeeva (Вопросы современной педиатрии)
The article reviews the issue of risk factors of early cardiovascular pathology of children suffering from juvenile rheumatic arthritis. It presents research findings of lipid metabolism, endothelium dysfunction, hem stasis system pathology of rheumatic arthritis and juvenile rheumatic arthritis. The article reveals the interaction between atherosclerosis pathogenesis and juvenile rheumatic arthritisKey words: juvenile rheumatic arthritis, aterothrombosis, atherosclerosis.